Determinants of Covid vaccine uptake and perinatal outcome in pregnant women at a tertiary care center - Sofia Butt,; Pooja Setlani,; Mehwish Iftikhar,; Samuel, Mehwish; Saba Rafiq Mughal,; Kashif Shafique,; Nazli Hossain, (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the factors for hesitancy and uptake of coronavirus disease-2019 vaccine, and to compare perinatal outcomes in vaccinated and nonvaccinated pregnant women. Method: The cross-sectional study was conducted from November 2021 to February 2022 at the Ruth Pfau Civil Hospital, Karachi, and the Holy Family Hospital, Karachi, and comprised pregnant women admitted in delivery suite for operative or vaginal delivery. Data was collected using a self-designed questionnaire which also explored knowledge about vaccine, contextual factors and reasons for and against vaccination. Perinatal outcomes included stillbirth, preterm delivery, low birth weight and Appearance-Pulse-Grimace-Activity-Respiration score. Also, 3cc blood was collected from the umbilical cord at the time of delivery, and enzyme-linked immunosorbent assay technique was used for antibodies titre. Data was analysed using SPSS 24. Results: Of the 186 women, 114(61.3%) with mean age 27.9±4.1 years were vaccinated, and 72(38.7%) with mean age 27.5±5.2 years were not vaccinated. Physician’s advise 104 (91.2%), vaccine safety and its effect on foetus 52(72.2%) were main determinants for vaccine uptake and refusal, repectively. Family and peer pressure was also responsible in 19(26.4%) cases for vaccine refusal. Body mass index, parity, level of education, socioeconomic status, history of coronavirus disease-2019 infection, booking status and presence of gestational diabetes mellitus were significantly different between the vaccinated and unvaccinated groups (p<0.05). Antibody titers and Appearance-Pulse-Grimace-Activity-Respiration score at 1 minute were significantly higher in the group of vaccinated women (p<0.05). Conclusion: Vaccine uptake was found to be low. Safety concern against vaccine, and doctor’s advice were the main determinants for hesitancy and uptake. Antibody titers in newborns were higher in the group of vaccinated women. Key Words: COVID-19 infection, Pregnancy, Vaccine, Antibody titers.